IMPLEMENTASI PENGUATAN PEDIDIKAN KARAKTER (PPK) NASIONALISME DAN RELIGIUS DALAM PEMBELAJARAN IPS DI SMP NASIMA SEMARANG - Lestari, Sri Puji; ., Tukidi; Hermanto, Fredy (Sosiolium: Jurnal Pembelajaran IPS, 2019)
The purposes of this research (1) to find out the Implementation of Nationalism and Religious Strengthening Character Education in learning social studies; (2) identify the supporting and inhibiting factors for the Implementation of Nationalism and Religious Strengthening Character Education in learning social studies at Junior High School of Nasima Semarang. The research method used was qualitative. The data collection techniques used were observation, interviews, and documentation. The data were analyzed using the Mile and Huberman Interactive Analysis.The data validity checking technique was using source triangulation. The results showed that: (1) the Implementation of Character buildings in learning social studies was carried out in all learning processes, including learning plan, learning implementation, and learning avaluation. (2) The barriers faced by social science’s teachers of Junior High School of Nasima Semarang were related to the efforts of consistency and continuity in internalizing the value of Character buildings,especially nationalism and religion character.The supporting factors for the mplementation of Nationalism and Religious Character buildings in learning social studies at Junior High School of Nasima Semarang were qualified teachers, and the complete facilities and infrastructure. Tujuan penelitian ini: (1) mengetahui implementasi PPK nasionalisme dan religius dalam pembelajaran IPS; (2) mengidentifikasi faktor pendukung dan penghambat implementasi PPK nasionalisme dan religius dalam pembelajaran IPS di SMP Nasima Semarang.Metode penelitian yang digunakan adalah kualitatif. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Data dianalisis menggunakan model Miles dan Huberman yaitu analisis interaktif. Teknik pemeriksaan keabsahan data dengan triangulasi sumber. Hasil penelitian menunjukkan bahwa: (1) Implementasi PPK Nasionalisme dan Religius dalam pembelajaran IPS dilakukan dalam semua proses pembelajaran, meliputi perencanaan pembelajaran, pelaksanaan pembelajaran, serta evaluasi pencapaian belajar; (2) Hambatan yang dihadapi guru IPS di SMP Nasima terkait dengan upaya konsistensi dan kontinuitas dalam menginternalisasikan nilai-nilai Penguatan Pendidikan Karakter (PPK) Nasionalisme dan Religius dalam diri siswa. Adapun faktor pendukung Implementasi PPK Nasionalisme dan Religius dalam pembelajaran IPS di SMP Nasima Semarang meliputi guru yang berkualitas, serta sarana dan prasarana yang lengkap.